Vaccine Assemblages on Three HPV Vaccine-Critical Facebook Pages in Denmark from 2012 to 2019 - Agergaard, Torben E. (2020)
Misinformation about vaccines on social media is a growing concern among healthcare professionals, medical experts, and researchers. Although such concerns often relate to the total sum of information flows generated online by many groups of stakeholders, vaccination controversies tend to vary across time, place, and the vaccine at issue. We studied content generated by administrators on three Facebook pages in Denmark established to promote critical debate about Human Papillomavirus (HPV) vaccination. We developed a qualitative coding frame allowing us to analyze administrators’ posts in terms of prevalent topics and intertextual material incorporated by linking and sharing. We coded more than a third of the posts (n = 699) occurring in the period from November 2012, when the first page was founded, to May 2019. We found that the pages mainly addressed the reports of adverse events following HPV vaccination and the (perceived) inadequate response of healthcare systems. To construct their central message, the pages assembled different sources, mostly reporting from Danish news media, but also personal narratives, scientific information, political assertions, and more. We conclude that HPV vaccination assemblages such as these pages are heterogeneous and contextual. They are not uniform sites of vaccine criticism, but rather seem to respond to and exchange information and misinformation within the communication environment in which they are embedded.